Construction of Φ43 diagrams for pedestrians - Mourrat, J; Weber, H; Xu, W (Springer, 2017)
We aim to give a pedagogic and essentially self-contained presentation of the construction of various stochastic objects appearing in the dynamical Φ43 model. The construction presented here is based on the use of paraproducts. The emphasis is on describing the stochastic objects themselves rather than introducing a solution theory for the equation.